Big endothelin-1 level is a useful marker for predicting the presence of isolated coronary artery ectasia. (19th May 2017) - Wang, Yao; Zhang, Yan; Zhu, Cheng-Gang; Guo, Yuan-Lin; Huang, Qiao-Juan; Wu, Na-Qiong; Gao, Ying; Qing, Ping; Liu, Geng; Dong, Qian; Li, Jian-Jun
Abstract: Context: Endothelin-1(ET-1) has been implicated in coronary artery disease (CAD) and may be associated with coronary artery ectasia (CAE). Objective: To clarify the relationship between big ET-1 and isolated CAE. Methods: We measured big ET-1 with ELISA in 216 patients (CAE, n  = 72; CAD, n  = 72; normal, n  = 72) and evaluated the link with isolated CAE. Results: The level of plasma big ET-1 was significantly higher in patients with isolated CAE ( p  < 0.001). Big ET-1 was strongly and independently associated with CAE by multivariate analysis (OR 95%CI: 1.026 (1.018–1.034), p  = 0.000). Conclusions: Big ET-1 may be a useful predictor for the presence of isolated CAE.